A historical comparative analysis of the community transformation of Tin Hau temples in Sai Kung and Shaukiwan. Issue 3 (4th June 2020) - Hung, Chung Fun Steven
Abstract : Purpose: This article investigates social history in Hong Kong and compares their community transformation with two Tin Hau temples in Hong Kong, namely the Sai Kung Tin Hau and Hip Tin Temple and Shaukiwan Tin Hau Old Temple. Design/methodology/approach: The paper is conducts a historical comparison to evaluate the vitality of traditional regions in Hong Kong with particular attention to the extent and intensity of its religious practice. Findings: The paper fills a gap in the literature by comprehensively investigating Chinese temple related societies and communities. Most previous studies of Chinese temples and their rituals have treated them in isolation from their political contexts, emphasizing topics such as iconography over details of temple communities and their relationships with other elements of the social structure. Originality/value: The research works from the point of view how the religious situation reflects important social characteristics and transformation of Shaukiwan and Sai Kung which were contemporary urban communities.